Answer CORRECTLY !!!!! Will mark brainliest !!!!!!!
![Answer CORRECTLY Will mark brainliest class=](https://us-static.z-dn.net/files/d1f/db71a24c8be66f9c28c70f4c9e25b951.png)
Answer:
Step-by-step explanation:
3a - 5 = -4b + 1
3a = -4b + 6
a = (-4b + 6)/3
h(a) = (-4b + 6)/3
Answer:
h(a) = [tex]\frac{6-3a}{4}[/tex]
Step-by-step explanation:
Given
3a - 5 = - 4b + 1
Rearrange making b the subject
Add 4b to both sides
4b + 3a - 5 = 1 ( add 5 to both sides )
4b + 3a = 6 ( subtract 3a from both sides )
4b = 6 - 3a ( divide both sides by 4 )
b = [tex]\frac{6-3a}{4}[/tex] , thus
h(a) = [tex]\frac{6-3a}{4}[/tex]